Nanotechnology in Oral Cancer Prevention and Therapeutics: A Literature Review - Kumar, Ritwika; Jha, Kunal; Barman, Diplina (Indian Journal of Medical and Paediatric Oncology, 2021)
The concept of nanotechnology revolves around the delivery of nano particle incorporated drugs which are originally engineered technology. Nanoparticles are used for targeted delivery and controlled release of a curative agents. Nanotechnology is gaining importance and is likely to be routine element of regular dental clinics. Nanomaterials are being incorporated in toothpastes, mouth rinses for improved efficiencies. It has found its use in restorative dental materials, anti-cariogenic enamel surface polishing agents, implant materials, etc. Few nanoparticles possess antimicrobial propertiesand intercepts bacterial activity. Nano dentistry is cost-effectiveness and timesaving compared to other techniques. Nano particles have also been beneficial to annihilate drug resistance, prevention of metastasis or lesion recurrence by earmarking malignant stem cells. Remarkable achievements were made in using nanoparticles for detecting and treating multiple variety of malignancies including colon cancer, prostate cancer, lung cancer, breast cancer, head and neck cancer, etc. This review was made to highlight the various clinical applications of nanotechnology in the diagnosis and curative care for oral cancer.
Keywords: oral cancer; nanotechnology; nanoparticles; cancer therapy; cancer prevention